From Ritual to Character: A Tri Hita Karana-Based Morning Assembly Model for Holistic Character Education in Early Childhood - Sari, Mekel Putu Ayu Sekar; Arnyana, Ida Bagus Putu; Bayu, Gede Wira (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to examine how a Tri Hita Karana-based Morning Assembly program functions as a holistic character education practice in early childhood education. Methodology: A qualitative case study was conducted in an early childhood education institution in Bali, implementing a Tri Hita Karana-based Morning Assembly program. Participants were selected using purposive sampling and included teachers directly involved in Morning Assembly, along with the school principal as a supporting informant. Data were collected through semi-structured in-depth interviews, participant observation, document analysis, and reflective field notes. Data were analyzed using reflexive thematic analysis to identify patterns across implementation structure, teacher mediation, internalization processes, and ecosystem reinforcement. Main Findings: The findings reveal that Morning Assembly operates through a structured three-phase sequence—pre-activity, core activity, and closing reflection—systematically embedding spiritual, social, and ecological values into daily routines. Teachers play a central mediating role by embodying and interpreting Tri Hita Karana values in relational practice. Character internalization occurs through repeated exposure, emotional engagement, reflective facilitation, and consistent reinforcement within a culturally coherent ecosystem. Novelty/Originality of this study: This study proposes a Holistic Character Education Model grounded in Tri Hita Karana, demonstrating how local philosophical wisdom can be operationalized into a structured pedagogical system in early childhood education. Unlike character education approaches that emphasize discrete moral instruction, the model conceptualizes character formation as a cyclical, ecosystem-based process that integrates spirituality, social harmony, and ecological responsibility into daily lived experience.